2015
DOI: 10.2337/db15-er03
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Placental Growth Factor Prevents Diabetic Retinopathy and Is Associated With Akt Activation and HIF1α-VEGF Pathway Inhibition. Diabetes 2015;64:200–212

Abstract: The Acknowledgments should read as follows: The authors thank Dr. Zhenhua Xu, Wilmer Eye Institute, for her helpful discussions about the WB experiments, and Dr. Junsong Gong, Wilmer Eye Institute, for his technical assistance. The Author Contributions should read as follows: H.H. designed the study, performed experiments, interpreted data, and wrote the manuscript. J.H., D.J., Y.W., Y.L., S.W., and E.J.D. performed experiments and interpreted data. G.A.L. and R.D.S. discussed the study and reviewed and edited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Finally, the loss of pericytes and endothelial cells causes capillaries occlusion and consequent ischemia. Retinal ischemia, through the activation of hypoxiainducible factor-1 (HIF-1) (Huang et al, 2015), determines an overproduction of vascular endothelial growth factor (VEGF), a key factor involved in both the progression of retinopathy towards PDR, and in DME development through phosphorylation of tight junction proteins such as occludin and zonula occludens-1 (Antonetti et al, 1999). Furthermore, VEGF, by the activation of the mitogen activated protein (MAP), stimulates the proliferation of endothelial cells, resulting in new vessels development (Rousseau et al, 1997).…”
Section: Diabetic Retinopathy: a Neurodegenerative Retinal Diseasementioning
confidence: 99%
“…Finally, the loss of pericytes and endothelial cells causes capillaries occlusion and consequent ischemia. Retinal ischemia, through the activation of hypoxiainducible factor-1 (HIF-1) (Huang et al, 2015), determines an overproduction of vascular endothelial growth factor (VEGF), a key factor involved in both the progression of retinopathy towards PDR, and in DME development through phosphorylation of tight junction proteins such as occludin and zonula occludens-1 (Antonetti et al, 1999). Furthermore, VEGF, by the activation of the mitogen activated protein (MAP), stimulates the proliferation of endothelial cells, resulting in new vessels development (Rousseau et al, 1997).…”
Section: Diabetic Retinopathy: a Neurodegenerative Retinal Diseasementioning
confidence: 99%
“…Previous studies showed that conbercept could specifically bind to PlGF in vitreous humor and was critical to the development of PDR [ 14 ]. In PlGF knockout mouse strain, its genetic deletion protects the retina from diabetic damaged by inhibiting Akt activation and the HIF1α-VEGF pathway [ 15 ]. This all suggested that PlGF could be another therapeutic target of conbercept.…”
Section: Discussionmentioning
confidence: 99%
“…We used C57BL/6J [C57] mice (PlGF +/+ control] and Akita [C57BL/6-Ins2 < Akita >/J], Akita.PlGF −/− [ C57BL/6-Ins2 < Akita > /J.PlGF −/− ] and PlGF −/− [ C57BL/6-PlGF −/− ] mice were generated and maintained as previously described 38 . Briefly, Akita mice were crossed with PlGF −/− mice 39 in a C57BL/6J background for two generations to give birth to the progeny with the genotype of Akita.PlGF −/− (Fig.…”
Section: Methodsmentioning
confidence: 99%